Pengaruh Celebrity Trustworthiness, Expertise, Attractiveness Selebriti Korea Selatan Terhadap Intensi Konsumen JABODETABEK Untuk Membeli Skincare Somethinc: Peranan Risk Perception Sebagai Mediator - Huang, Lydia Margaretha; Christanto, Budi (Universitas Bunda Mulia, 2024)
One form of modern marketing that is popular and often found everywhere is celebrity endorsement. It is known that celebrity endorsements make it easier for consumers to remember a brand. As one of Indonesia's local skincare brands, Somethinc also uses celebrities to market its products. The aim of this research is to see the influence of celebrity trustworthiness, celebrity expertise, and celebrity attractiveness on consumer buying intention with perceived risk as a mediator. This research has collected a sample of 147 respondents spread across the JABODETABEK area using a Likert scale and processed using SmartPLS 3. This research is quantitative research. The results of this research show that the variables celebrity trustworthiness and celebrity expertise do not influence consumer buying intention either through a mediator or without a mediator. Meanwhile, the celebrity attractiveness variable influences consumer buying intention, where the perceived risk variable partially provides significant results on the influence of celebrity attractiveness on consumer buying intention.